Solving the multiobjective environmental/economic dispatch problem using weighted sum and ε -constraint strategies and a predictor-corrector primal-dual interior point method - De Lorena Stanzani, Amélia [UNESP]; Balbo, Antonio Roberto [UNESP]; Nepomuceno, Leonardo [UNESP]; Baptista, Edméa Cássia [UNESP] (Springer Nature, 2014)
This paper proposes a technique for solving the multiobjective environmental/economic dispatch problem using the weighted sum and \varepsilon ε -constraint strategies, which transform the problem into a set of single-objective problems. In the first strategy, the objective function is a weighted sum of the environmental and economic objective functions. The second strategy considers one of the objective functions: in this case, the environmental function, as a problem constraint, bounded above by a constant. A specific predictor-corrector primal-dual interior point method which uses the modified log barrier is proposed for solving the set of single-objective problems generated by such strategies. The purpose of the modified barrier approach is to solve the problem with relaxation of its original feasible region, enabling the method to be initialized with unfeasible points. The tests involving the proposed solution technique indicate i) the efficiency of the proposed method with respect to the initialization with unfeasible points, and ii) its ability to find a set of efficient solutions for the multiobjective environmental/economic dispatch problem. © 2014 Brazilian Society for Automatics - SBA.
Keywords: Environmental/economic dispatch problems; Modified barrier; Predictor-corrector primal-dual interior point method